Missions in a changing world: the Bundeswehr and its operations abroad - Glatz, Rainer; Hansen, Wibke; Kaim, Markus; Vorrath, Judith (2018)
Abstract: Military operations abroad by the German Armed Forces are always a controversial instrument of German crisis management. Yet, such foreign deployments are likely to remain necessary for the foreseeable future while, at the same time, they are undergoing noticeable change. The conditions shaping this transformation can be captured in three dimensions of change: the change in war and violent conflict; the transformation of the international political and legal context; and the shifting institutional frameworks for these operations. German policy-makers must address the related challenges - whether setting normative anchors and formats for operations, contributing to stabilisation in a context of continuing insecurity, building partners’ military capacities, dealing with transnational threats or using benchmarks for exiting. Yet, they only have limited influence over the described changes. Fundamentally, decisions about military operations abroad are taken within the triangle of p